Meet the iPad (third generation) - Carlson, Jeff (Peachpit Press, 2012)
This invaluable guide to the new, third-generation iPad steers you through how to navigate the home screen; buy, launch, run, and switch between apps; change and lock screen orientation, adjust screen brightness; and conserve battery life. You'll learn how to master Multi-Touch gestures, work with text, shoot video and photos using the two built-in cameras, make FaceTime calls, sync files and content with iCloud, connect to the Internet using a Wi-Fi or 4G network, link up with Bluetooth devices, mirror video, and search using Spotlight. This practical, approachable guidebook by Apple guru Jeff Carlson will quickly help you get the most out of your third-generation iPad!